Groundwater Effect on Slope Stability in Open Pit Mining: a Case of West Kutai Regency, East Kalimantan, Indonesia - Shalaho Dina Devy; Pretty Permatasari Hutahayan (UIR PRESS, 2021)
The stability of open pit slopes in Biangan district, West Kutai Regency, East Kalimantan Province, is greatly influenced by groundwater conditions. The existence of groundwater reduces the shear strength of the materials which causes a decrease in the stability value of pit slopes. The main objective of this study is to assess the impact of groundwater on the stability of the low wall and high wall pit mining. Groundwater modeling is used to determine the prediction of groundwater level on the pit slope which determines the value of the slope stability. Slope stability analysis in this study was performed using the Finite Element Method, producing output in the form of strain zones, deformation and displacement values. Therefore, the Strength Reduction Factor (SRF) approach was used, which is a gradual reduction of shear strength until the values of cohesion and friction angles reach minimums and the slopes are at a critical state. Groundwater modeling results indicate that groundwater flows to the Biangan river with hydraulic heads between 76 and 108 meters above sea level. Based on the analysis using the Finite Element Method, the stability values of the pit slopes, which are influenced by groundwater, are 0.65 on the low wall and 1.40 on the high wall. The total displacements are 0.019 meters on the low wall and 0.002 meters on the high wall. The impact of groundwater on the slope is an increase in the slope load. This increases the materials’ thrust and reduces the shear strength of the materials which reduces the rock mass that can function as a water seepage path. Thus, the recommendation for low wall pit construction is a safety factor of 7.79 with a total displacement of 0.020 meters.